Improving Students' Vocabulary Mastery By Using U-Dictionary - Mustika, Yeni; Dashela , Tarina (LPPM STBA Pontianak, 2024)
The teacher found several vocabulary problems faced by the students during teaching and learning English. The students were lack of vocabulary mastery, had difficulty in memorizing the word, sometimes missed spelling the word, and the difficulty pronouncing the words and finding the word's meaning. They were difficult to recognize the word classes such as nouns, verbs, adjectives, and adverbs effectively. For this reason, the researcher brought U-dictionary as media to improve students' vocabulary mastery. The classroom action research method with two cycles was used in this research. The subject was the second-semester students of Bina Sarana Informatika University consisting of 46 students. The observation and measurement techniques were used as the technique of collecting data. The observation checklists, field notes, interviews, and tests were used as the instruments for collecting data. The result showed that the use of U-Dictionary could help the teacher to improve the student's vocabulary mastery effectively. It served as a fun and simple way of learning activity. U-Dictionary led the students to build up their motivation and interest during the teaching and learning process.